Diagnosis and classification of headache associated with sexual activity using a composite algorithm: A cohort study. (December 2021) - Lin, Po-Tso; Wang, Yen-Feng; Fuh, Jong-Ling; Lirng, Jiing-Feng; Ling, Yu-Hsiang; Chen, Shih-Pin; Wang, Shuu-Jiun
Background: To differentiate primary headache associated with sexual activity from other devastating secondary causes. Methods: In this prospective cohort, we recruited consecutive patients with at least 2 attacks of headache associated with sexual activity from the headache clinics or emergency department of a national medical center from 2005 to 2020. Detailed interview, neurological examination, and serial thorough neuroimaging including brain magnetic resonance imaging and magnetic resonance angiography scans were performed on registration and during follow-ups. Patients were categorized into four groups, i.e. primary headache associated with sexual activity, reversible cerebral vasoconstriction syndrome, probable reversible cerebral vasoconstriction syndrome, and other secondary headache associated with sexual activity through a composite clinic-radiological diagnostic algorithm. We compared the clinical profiles among these groups, including sex, age of onset, duration, quality, and clinical course ("chronic" indicates disease course ≥ 1 year). In addition, we also calculated the score of the reversible cerebral vasoconstriction syndrome2, a scale developed to differentiate reversible cerebral vasoconstriction syndrome from other intracranial vascular disorders. Results: Overall, 245 patients with headache associated with sexual activity were enrolled. Our clinic-radiologic composite algorithm diagnosed and classified all patients into four groups, including 38 (15.5%) with primary headache associated with sexual activity, 174 (71.0%) with reversible cerebral vasoconstriction syndrome, 26 (10.6%) with probable reversible cerebral vasoconstriction syndrome, and 7 (2.9%) with other secondary causes (aneurysmal subarachnoid hemorrhage (n = 4), right internal carotid artery dissection (n = 1), Moyamoya disease (n = 1), and meningioma with hemorrhage (n = 1)). These four groups shared similar clinical profiles, except 26% of the patients with primary headache associated with sexual activity had a 3 times greater chance of running a chronic course (≥ 1 year) than patients with reversible cerebral vasoconstriction syndrome. Of note, the reversible cerebral vasoconstriction syndrome2 score could not differentiate reversible cerebral vasoconstriction syndrome from other groups. Conclusion: Our composite clinic-radiological diagnostic algorithm successfully classified repeated headaches associated with sexual activity, which were predominantly secondary and related to vascular disorders, and predicted the prognosis. Primary headache associated with sexual activity and reversible cerebral vasoconstriction syndrome presented with repeated attacks of headache associated with sexual activity may be of the same disease spectrum.